Analisis Pembangkit Listrik Tenaga Mikro Hidro (PLTMH) Studi Kasus : Sungai Air Anak (Hulu Sungai Way Besai) - Dwiyanto, Very; Kusumastuti, Dyah Indriana; Tugiono, Subuh (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
This research was conducted in order to calculate the reduction in electrical power that can be generated by a micro-hydro power plant in Air Anak river. The decline in power at the micro-hydro power plant Air Anak river is caused by the presence of sediments that accumulate in the weir micro-hydro power plants, so that reduced water storage that can be streamed to a penstock pipe to generate electrical power. In this study, carried out calculations mainstay river discharge Air Anak by comparison mainstay river discharge Way Besai obtained from the data processing streamflow recorder at the hydroelectric plant reservoirs Way Besai for 11 years from 2004 to 2014 using the Flow Duration Curve method, calculation of electric power generated from the design discharge on micro-hydro power plant Air Anak, calculation of reduction in electrical power at the micro-hydro power plant Air Anak. From the research, design discharge value obtained micro-hydro power plant Air Anak is equal to 0,2565 m3/s with power generated by 2,1962 kW. Power reduction is calculated based on measurements taken 2 times. In streamflow measured at 1,1923 m3/s, water can flow into the pipe by 7 cm generate a discharge of 0,0592 m3/s. Power that can be generated at 1,2326 kW or by 56,12 % of the generated design power. In streamflow measured at 0,5788 m3/s, water can flow into the pipe by 4 cm generate a discharge of 0,0189 m3/s. Power that can be generated at 0,4062 kW or by 18,50 % of the generated design power. Keywords : micro hydro, flow duration curve, electricalpower